MODELING TABAT EFFECT INUNDATION IN THE PEAT SWAMP FOREST CENTRAL KALIMANTAN - Petrisly Perkasa (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2016)
Peat swamp forests serve as an abundant water catchment area in rainy season and then releases it gradually in dry season. The main function of peat swamp forests are as the hydrology regulator in an ecosystem, and the function will be disrupted when the peat swamp forests have excessive drainage condition. Recently, the peat swamp forests of Central Kalimantan are badly damaged by prolonged exploration without any responsibility to preserve it. One of the damage causes of the peat swamp forests in Central Kalimantan are many canals made when illegal loggers get their harvested wood out to the estuary of nearest watershed. Therefore, it forms canals that drain water with no control. The effect is peat swamp forests will be very dry and trigger devastating fire that cannot be extinguished in a short time. One of the efforts to deal with the problem is by recovering the hydrology condition of peat swamp forests ecosystem through duct insulation using simple dam locally called “tabat”. The making of tabat is easily designed in order that the implementation is not very hard, and the material selection such as forest wood dominate the construction because the wood will be cracked gradually without disturbing the ecosystem process and restoration principle in peat swamp forests. The modeling result by a computer software of hydraulics shows the increase of water level in canals at 15 to 30 cm and the width of inundation in tabat when the designed flood of two-year return period was modeled to 280.67 km2 and for the period of five years was 306.04 km2 from the target of hydrology restoration of 250 km2.